Basic skills in English : Yellow level - Littell, Joy (The McDougal, Littell english program, 1985)
The book covers grammar, vocabulary, reading comprehension, and writing exercises, helping learners build a solid foundation for effective communication. Its structured lessons and practice activities aim to improve students' confidence and proficiency in English.